2017
DOI: 10.5505/pajes.2016.94546
|View full text |Cite
|
Sign up to set email alerts
|

Real-time speed controlling of a DC motor using fuzzy logic controller

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The results presented were from tests that solely involved an open-loop speed controller. In a related study, the implementation of the speed control of a DC motor was demonstrated [19] using a fuzzy logic controller with the speed error and change in speed error as inputs to the fuzzy controller. The speed controller was tested with a multifunctional data acquisition device NI USB-6812 DAQ card and MS15 DC motor control module.…”
Section: Introductionmentioning
confidence: 99%
“…The results presented were from tests that solely involved an open-loop speed controller. In a related study, the implementation of the speed control of a DC motor was demonstrated [19] using a fuzzy logic controller with the speed error and change in speed error as inputs to the fuzzy controller. The speed controller was tested with a multifunctional data acquisition device NI USB-6812 DAQ card and MS15 DC motor control module.…”
Section: Introductionmentioning
confidence: 99%
“…In [20], in order to control the system, Quanser Q8 data acquisition card along with high performance computers were used for sending analog signals and getting encoder signals. In [21], the data exchange with the PC was provided by a NI USB-6812 DAQ card, which sent the signals that it received from the feedback tacho generator and control signals to the DC motor control module. In both cases vast resources were used for the control of DC motor.…”
Section: Introductionmentioning
confidence: 99%